Interest Rate Liberalization in China - Feyzioglu, Tarhan (IMF Working Papers; Working Paper ;, 2009)
What might interest rate liberalization do to intermediation and the cost of capital in China? China's most binding interest rate control is a ceiling on the deposit rate, although lending rates are also regulated. Through case studies and model-based simulations, we find that liberalization will likely result in higher interest rates, discourage marginal investment, improve the effectiveness of intermediation and monetary transmission, and enhance the financial access of underserved sectors. This can occur without any major disruption. International experience suggests, however, that achieving these benefits without unnecessary instability, requires vigilant supervision, governance, and monetary policy, and a flexible policy toolkit.